2022
DOI: 10.1021/acsami.2c16242
|View full text |Cite
|
Sign up to set email alerts
|

Method to Inhibit Perovskite Solution Aging: Induced by Perovskite Microcrystals

Abstract: The main feature of perovskite solar cells (PSCs) is that the perovskite layer can be fabricated by the solution method, while the long-time stability of the precursor solution is critical. During the fabrication of formamidinium (FA)-based PSCs, the introduction of methylammonium cations (MA+) in the precursor solution can accelerate the crystallization process of the perovskite layer, stabilize the perovskite structure, and passivate defects. However, MA+ is easy to deprotonate to generate MA molecules, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…It is worth noting that we employ FAPbI 3 single crystals to prepare the precursor solution instead of using FAI and PbI 2 . This choice minimizes the influence of impurities in PbI 2 . , The precursor solution undergoes aging in a glovebox with inert nitrogen gas at room temperature (25 °C), effectively eliminating the influence of external environmental factors such as water, oxygen, and temperature. ESI-MS technology is used to detect the reaction products of the aging solution …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that we employ FAPbI 3 single crystals to prepare the precursor solution instead of using FAI and PbI 2 . This choice minimizes the influence of impurities in PbI 2 . , The precursor solution undergoes aging in a glovebox with inert nitrogen gas at room temperature (25 °C), effectively eliminating the influence of external environmental factors such as water, oxygen, and temperature. ESI-MS technology is used to detect the reaction products of the aging solution …”
Section: Resultsmentioning
confidence: 99%
“…Several factors affect the reactivity of FAPbI 3 perovskites in the presence of MA + cations. First, temperature is the most critical factor affecting the deprotonation of MA + ; higher temperatures promote the deprotonation of MA + . , Second, alkaline impurities in PbI 2 have also been found to be important factors in inducing deprotonation and subsequent reactions. , However, some studies have reported that Lewis base additives could stabilize the precursor solution and inhibit the generation of MFAI. ,,, At the same time, other literatures persist that Lewis acid additives could inhibit the generation of MFAI. ,, These results indicate that the aging mechanism of the FAPbI 3 perovskite precursor solution is still very complex and unclear. Another factor that cannot be ignored for the aging of the precursor solution is the solvent itself.…”
Section: Introductionmentioning
confidence: 98%
“…Short-term and long-term stability of precursors is critical in perovskite solution systems. [58][59][60] On the one hand, aging of the precursor affects the crystallinity of the MHP SCs. It has been reported that with the increase of aging resistance time of precursor solution, the colloid clusters in solution can maintain a larger volume for a long time.…”
Section: A Specific Description Of the Precursor Statementioning
confidence: 99%
“…Spin-coating process is relatively simple, which is the current method of perovskite light absorption layer. According to the different steps can be further divided into one-step process [4][5][6] , and two-step process [7,8] . Among them, the one-step process refers to add all the raw materials of perovskite into the solvent, and then form the precursor solution after completely dissolved.…”
Section: Introductionmentioning
confidence: 99%